Treatment of obstetric post-dural puncture headache. Part 2: epidural blood patch. (May 2019) - Russell, R.; Laxton, C.; Lucas, D.N.; Niewiarowski, J.; Scrutton, M.; Stocks, G.
Highlights: Postnatal headache may be associated with maternal mortality. The management of obstetric post-dural puncture headache (PDPH) varies considerably. Much of the evidence on obstetric PDPH management is not of high quality. Recommendations for treatment with an epidural blood patch are made. Women experiencing PDPH should be followed-up after hospital discharge. Abstract: The 2009–12 MBRRACE-UK report highlighted the deaths of two women in whom dural puncture had occurred during insertion of a labour epidural catheter. Despite suffering long-term headaches, neither woman was adequately followed-up after discharge from hospital. Death resulted from a cerebral vein thrombosis in one case and a subdural haematoma in the other. Due to significant variation in the treatment of obstetric post-dural puncture headache, an Obstetric Anaesthetists' Association working group was set up to produce evidence-based guidelines to guide clinicians. These guidelines have been condensed into two review articles. In this second review, the role of an epidural blood patch is discussed using a question and answer format.